AKAL DALAM PERSPEKTIF PENDIDIKAN ISLAM (TELAAH REFLEKTIF FILSAFAT PENDIDIKAN ISLAM TERHADAP AYAT-AYAT ALQURAN) - Wasehudin Wasehudin (Al Qalam, 2018)
The search of a divine messages understanding should be sought in the newest formulation, so that the Scripture can provide a brilliant and glorious answer or it will be soothing the truth’s seeker in all problem forms, which is from the past, the present, and the future. The exclamation in the language of The Qur’an was revealed in various words forms: afala ta’qiluun, afala tatadabbarun, afala tubshirun and etcetera. Those words are a series of bids for people to constanly explore, make a review, and also do research through of education as the Caliphate task. The mind of this educational philosophy perspective is like two sets of the coin that cannot be separated from one another. If philosophy was crowned as “The Mother of Science” or The Mother of all Science kind, then of course mind will be the sun of science and the main media in the world of education.